Clinical associations of temporomandibular disorder and bruxism related symptoms with periodontal disease progression - Werner, Nils; Heck, Katrin; Ern, Christina; Heym, Richard; Le, Vinzenz; Schubert, Oliver; Wetzel, Charlotte; Pitchika, Vinay; Schwendicke, Falk; Folwaczny, Matthias; Bumm, Caspar Victor (Frontiers in Oral Health, 2025)
IntroductionThe aim of this study was to analyse whether symptoms of temporomandibular disorders (TMD) or bruxism were associated with the progression of periodontitis. A potential association could be explained by a decreased level of oral hygiene in patients presenting with orofacial pain.Materials and methods148 patients diagnosed with periodontitis received individual department specific screening for symptoms of TMD or bruxism prior to initial treatment and were stratified into patients with symptoms related to TMD or bruxism (STMDoB = 30) and without symptoms (NO_STMDoB = 118). Progression of periodontitis was determined by tooth loss (TL) as well as radiographic bone loss (RBL), using longitudinal radiographic data with a follow-up of at least 5 years.ResultsPatients presented with a median of 60 [52;68] years, 25 [21;27] teeth and a mean RBL of 50.5 ± 16.4% not showing difference among both study groups. Neither RBL [1.2 [0.0;6.0] % STMDoB vs. 2.9 [0.0;9.1] % NO_STMDoB, p = 0.165] nor TL [1 [0;3] STMDoB vs. 1 [0;3] NO_STMDoB; p = 0.195] differed significantly between both study groups, with equally low periodontal progression in both groups. Regression models revealed no association of any reported symptom of TMD or bruxism with periodontal progression (β: 9.07; CI: −4.09;22.23; p = 0.446 for RBL and rate ratio: 1.09; CI: 0.80;1.47; p = 0.587 for TL).ConclusionsThe present data showed no association of STMDoB with periodontal disease progression on the patient level.